Solvation and cavity occupation in biomolecules - Lynch, Gillian C.; Perkyns, John S.; Nguyen, Bao Linh; Pettitt, B. Montgomery (Biochimica et biophysica acta, 2015)
Solvation density locations are important for protein dynamics and structure. Knowledge of the preferred hydration sites at biomolecular interfaces and those in the interior of cavities can enhance understanding of structure and function. While advanced X-ray diffraction methods can provide accurate atomic structures for proteins, that technique is challenged when it comes to providing accurate hydration structures, especially for interfacial and cavity bound solvent molecules. Advances in integral equation theories which include more accurate methods for calculating the long-ranged Coulomb interaction contributions to the three-dimensional distribution functions make it possible to calculate angle dependent average solvent structure, accurately, around and inside irregular molecular conformations. The proximal radial distribution method provides another approximate method to determine average solvent structures for biomolecular systems based on a proximal or near neighbor solvent distribution that can be constructed from previously collected solvent distributions. These two approximate methods, along with all-atom molecular dynamics simulations are used to determine the solvent density inside the myoglobin heme cavity. Myoglobin is a good test system for these methods because the cavities are many and one is large, tens of Å3, but is shown to have only four hydration sites. These sites are not near neighbors which implies that the large cavity must have more than one way in and out. Our results show that main solvation sites are well reproduced by all three methods. The techniques also produce a clearly identifiable solvent pathway into the interior of the protein. The agreement between molecular dynamics and less computationally demanding approximate methods is encouraging. This article is part of a Special Issue entitled Recent developments of molecular dynamics. [Display omitted] •Solvent in interior cavities is important for protein function.•Approximate density distributions compare well with molecular dynamics densities.•Approximate distribution function reconstructions are computationally inexpensive.